Bond-Alternating Antiferromagnetic S=1/2 Heisenberg Ladder with Ferromagnetic Diagonal Coupling - 李安康 路俊哲 马雷 (Chinese physics letters, 2009)
Using the density matrix renormalization group method, we determine the phase diagram of a frustrated bond-alternating S=1/2 Heisenberg ladder with ferro-antiferromagnetic couplings at zero temperature. With the interactions between spins along the rungs set, we identify three spin-gapped phases （the Haldane phase, the singlet phase and the dimer phase） in the whole parameter range. The analysis of our data shows that two-leg spin bond-alternating ladders have a rich phase diagram if both rung and diagonal couplings are taken into account.